A study on clinical and epidemiological profile of patients admitted with white patch in throat to Sir Ronald Ross Institute of Tropical and Communicable Diseases, Hyderabad, India - ., Asma; Ivaturi, Phani Bhushan (International Journal Of Community Medicine And Public Health, 2018)
Background: One of the most common differential diagnosis for a white patch in throat is diphtheria. Diphtheria is an acute infectious disease caused by toxigenic strains of corynebacterium diphtheriae. These bacilli release powerful exotoxin which is responsible for formation of white or greyish or yellowish membrane commonly over tonsils, pharynx or larynx. The objectives of the study were to determine the clinical and epidemiological factors of cases admitted with white patch in throat; to assess the microbiological confirmation rate of diphtheria among cases with white patch in throat; to identify the mortality and morbidity among study population. Methods: A cross sectional record based retrospective study was carried out at Sir Ronald Ross Institute of Tropical & Communicable Diseases, Hyderabad. All the cases admitted in year 2016 with a white/grey/yellowish patch in throat were included in the study. The study was carried out for 2 months. Results: A total of 230 cases were reported and 46.1% of cases were in the age group of 11-20 years. Males constituted about 48.3% and females 51.7% of study population. The most common clinical presentation was Sore throat, fever and a pseudo membrane over tonsils/pharynx. A total of 12 deaths occurred among 230 cases. Conclusions: Deaths occurred most commonly in the younger age group and in the non-immunized. Recovery was faster and the course of illness was uncomplicated in the older age group and in completely immunized individuals.